2019
DOI: 10.1177/1071100719873971
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the Lateral Plantar Ligaments of the Transverse Metatarsal Arch

Abstract: Background: While the anatomy of the Lisfranc complex is well understood, the lateral tarsometatarsal ligamentous structures, in contrast, are less well studied. Our aim in this study was to identify an anatomical explanation as to why the second to fifth metatarsals function as a unit in homolateral and divergent midfoot injuries. Methods: Eleven cadaveric lower limbs, preserved in formaldehyde, were examined at the University of Liverpool Human Anatomy and Resource Centre. Each of the lower limbs was dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
0
11
3
Order By: Relevance
“…Previous studies reported that dorsal tarsometatarsal ligaments occurred in 7–9 distinct bands, interosseous intermetatarsal ligaments occurred in 4 distinct bands, and plantar tarsometatarsal bands occurred in 9 separate bands (Castro et al, 2010; Sarrafian, 2011; Ulbrich et al, 2013; Won et al, 2019). Further, Mason et al (2020) identified a well‐defined ligament originating from the base of M5 and inserting on the lateral plantar aspect of M2, and that this ligament was present in all 11 specimens; however, the sample size was very small (n = 11) compared with that in the present study (n = 100). Factors related to dissection also need to be considered: Mason et al (2020) reported that the LPL blended partially with the lateral plantar ligament in the medial third of the ligament in all specimens.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…Previous studies reported that dorsal tarsometatarsal ligaments occurred in 7–9 distinct bands, interosseous intermetatarsal ligaments occurred in 4 distinct bands, and plantar tarsometatarsal bands occurred in 9 separate bands (Castro et al, 2010; Sarrafian, 2011; Ulbrich et al, 2013; Won et al, 2019). Further, Mason et al (2020) identified a well‐defined ligament originating from the base of M5 and inserting on the lateral plantar aspect of M2, and that this ligament was present in all 11 specimens; however, the sample size was very small (n = 11) compared with that in the present study (n = 100). Factors related to dissection also need to be considered: Mason et al (2020) reported that the LPL blended partially with the lateral plantar ligament in the medial third of the ligament in all specimens.…”
Section: Discussioncontrasting
confidence: 61%
“…The morphological characteristics of the lateral plantar ligament were assessed and its length, width, and thickness of the fiber bundles were measured according to a method described previously (Mason et al, 2020). Measurements were made at the center of all ligaments using digital calipers (Shinwa Rules, Niigata, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…42 As a result, the lateral column is generally not fused in the treatment of Lisfranc injuries and is allowed to remain mobile. Recently, Mason et al 36 described the lateral Lisfranc ligament, a transverse suspensory metatarsal ligament that connects the long plantar ligaments of both the transverse and longitudinal arches. In cadavers, they noted that this ligament allowed M2 through M5 to act as a single unit.…”
Section: Anatomymentioning
confidence: 99%